Improved Alkyl Glycoside Synthesis by trans‐Glycosylation through Tailored Microenvironments of Immobilized β‐Glucosidase. Issue 1 (9th January 2020) - Hoffmann, Christian; Grey, Carl; Pinelo, Manuel; Woodley, John M.; Daugaard, Anders E.; Adlercreutz, Patrick
Abstract: We present how the microenvironment can directly improve biocatalytic selectivity of immobilized β‐glucosidase. β‐Glucosidase from Thermotoga neapolitana was immobilized on a variety of functionalized off‐stoichiometric thiol‐ene (OSTE) particles, where highest activities were observed for thiol and imidazole functional particles. Compared to the soluble enzyme, the selectivity (rs /rh ) between trans‐glycosylation of p‐nitrophenyl β‐D‐glucopyranoside (pNPG) with 1‐propanol over hydrolysis was increased by a factor of 2–3 using particles containing imidazole (rs /rh of 6.7) and carboxylic acid moieties (rs /rh of 9.2), respectively. These results demonstrate clearly that enzyme selectivity depends directly on the local environment of the enzyme with the support. Abstract : The impact on activity and selectivity as an effect of the local microenvironment was investigated for immobilized β‐glucosidase from Thermotoga neapolitana . The enzyme was immobilized on thiol‐ene (OSTE) particles having hydrophilic, hydrophobic, hydrogen‐accepting and hydrogen‐donating surfaces. Compared to the soluble enzyme, the selectivity between trans‐glycosylation of p ‐nitrophenyl β‐D‐glucopyranoside (pNPG) with 1‐propanol over hydrolysis was significantly increased for imidazole and carboxylic acid surfaces.